Pengabdian kepada Masyarakat melalui Kuliah Kerja Nyata (KKN) di Desa Pematang Johar Kabupaten Deli Serdang - Moh. Rizky Ramadhan; Bayu Pradana; Athaya Raissa; Shelly Tipany; Nefi Darmayanti (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Pematang Johar Village is a village in Labuhan Deli District, Deli Serdang Regency, which has great potential in the social, religious, and economic fields of the community. This study aims to describe the socio-religious conditions and the role of the community in maintaining local religious and cultural values ​​​​amidst the flow of modernization. The research method used is the Participatory Action Research (PAR) method. Where researchers together with the community actively plan and implement the programs carried out. This village is the location of the Community Service Program (KKN) by Uinsu students, who carry out various programs to address social, economic, and educational challenges in the village. The KKN programs implemented include mutual cooperation, religious moderation with socialization of increasing religious values. Empowerment of digital-based MSMEs to increase the marketing of Johar Clean dishwashing soap products. Anti-bullying workshops, legal protection and business in Islam at local elementary schools. In addition, the KKN program also seeks to increase interest in education in the village by holding private tutoring, regular Quranic recitations, and teaching activities at schools.